Efeito da desidratação osmótica no acúmulo de prolina livre em discos foliares de vinte cultivares de feijão (Phaseolus vulgaris L) - Machado , Regina C R; Braga Rena, Alemar; Vieira , Clibas (Revista Ceres, 2025)
Changes in the content of free proline in osmotic dehydrated discs of the primary leaves of 20 bean (Phaseolus vulgaris L.) cultivars are discussed. There are differences among the cultivars in relation to their content of free proline in turgid leaf discs. All cultivars accumulated high levels of free proline as compared to the turgid control both in the mild (-10 atm /30 hours) and severe (-20 atm/15 e 30 hours) osmotic desiccation. The data indicate that the cultivars could be separated into three groups according to their ability to accumulate proline: high, intermediate and low accumulators. The cultivars ‘Manteigao Fosco 11’ and ‘Vermelho Rajado 1162' accumulated the most and the ‘Rico-23' the least proline.